Personality Traits that Predict the Burnout Syndrome on Mexican Teachers - Villaverde, Diego (2019)
The objective of the study was to determine the predictive value of personality traits according to the Mexican model of the Five Personality Factors in the Burnout Syndrome (BOS) and its dimensions from the Gil-Monte model. Three hundred and seventy-five basic education teachers from Mexico City took part in it. The sampling was intentional, non-probabilistic with cross-sectional and correlational design. The Spanish Burnout Syndrome inventory and the Mexican Five Personality Factors scale were used. Pearson's Correlation Test and a stepwise linear regression model were employed for the analysis. With the exception of Emotional Control and Enthusiasm towards work (r2=.087; p>0.05), the results found significant correlations of the Five Mexican personality factors and BOS, negative in the case of personality traits and Psychic Burnout, Indolence, and Guilt; and positive among personality factors and enthusiasm towards work. The multiple linear regression model included Expressive Sociability, Organization and Acceptableness as BOS predictors (F= 39.8, β=-.197*). Therefore, it is concluded that these are the personality traits associated with the syndrome that have a flexible role in the development of BOS. The results also coincide with other studies. It is suggested for further research to evaluate the modulating role of these traits with Psychosocial Risk Factors as an antecedent.